Nature of inflows and outflows in AGNs. Issue Volume 15:Issue S359(2020) (March 2019) - Wada, Keiichi; Kudoh, Yuki; Yutani, Naomichi; Kawakatu, Nozomu
Abstract: Despite many theoretical studies and observations, we still do not fully understand the feeding mechanism in AGNs even in nearby galaxies, and how feedback from AGNs affects the gas dynamics itself in the galactic central regions. In this article, we summarize our recent theoretical studies and preliminary results in terms of the mass inflow and outflows on sub-parsec to 100 parsecs scales around AGNs. We introduce different studies: 1) How do galaxy-galaxy mergers trigger AGN activity and obscuration?, 2) How do the radiative feedback affect formation of outflows and obscuration of the nucleus? and 3) How does the AGN plus starburst feedback contribute to the obscuration?